2012
DOI: 10.4187/respcare.01446
|View full text |Cite
|
Sign up to set email alerts
|

Expectant Management of Pneumothorax in Preterm Infants Receiving Assisted Ventilation: Report of 4 Cases and Review of the Literature

Abstract: Pneumothorax is a common complication in infants receiving assisted ventilation. The appropriate management of this condition is not always clearly defined, especially when a large air leak and mediastinal shift are present but the infant is hemodynamically stable. Despite the complications associated with chest tube placement, this remains the most common approach in such cases. We report 4 cases of preterm infants who developed large pneumothoraces with mediastinal shift while on assisted ventilation and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The presence of persistently high or unequal transpulmonary inflating pressure in the alveoli during the transition period results in rupture of alveoli into the pleural space and produces a spontaneous pneumothorax 6 . The incidence of radiologic SP is 1% to 2% and symptomatic SP is 0.05% to 1% in all live births and in very low birth weight (VLBW) neonates this rate can achieve 3.8% to 9% 1,7,8 . The incidence rate can increase to up to 30% in patients who have concurrent underlying lung disease or who require mechanical ventilation 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of persistently high or unequal transpulmonary inflating pressure in the alveoli during the transition period results in rupture of alveoli into the pleural space and produces a spontaneous pneumothorax 6 . The incidence of radiologic SP is 1% to 2% and symptomatic SP is 0.05% to 1% in all live births and in very low birth weight (VLBW) neonates this rate can achieve 3.8% to 9% 1,7,8 . The incidence rate can increase to up to 30% in patients who have concurrent underlying lung disease or who require mechanical ventilation 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently Kitsommart et al [ 4 ] reported 4 cases of preterm infants who developed large pneumothoraces, two of whom remaining on nasal CPAP after the diagnosis. In our experience, all the neonates developed worsening respiratory severity in terms of increasing of respiratory rate, Silverman score, FiO 2 requirement and PCO 2 values, making intubation mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…A 40% increase of FiO 2 during the first 24 h of CPAP has been suggested as a useful marker to identify the infants at high risk of developing a pneumothorax [ 3 ]. Recently successful management strategies have been reported of symptomatic pneumothorax diagnosed in preterm infants receiving assisted ventilation, which avoided chest tube drainage and resulted in reduction of important side effects [ 4 , 5 ]. In this case series, we reported our experience of using high-frequency oscillatory ventilation (HFOV) as a first-line treatment of pneumothorax in preterm infants with respiratory distress syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…17,19,20 Although some infants may be managed expectantly, many have acute decompensation requiring immediate intervention with chest tube placement. 17,[20][21][22] Incorrect placement of chest tubes may be associated with serious complications, including perforation of the lung 23 ; misplacements into the liver, peritoneal space, heart, spleen, subclavian vessels, colon, esophagus, and inferior vena cava 24 ; and phrenic nerve paralysis. 25 All practitioners who take care of critically ill infants should learn to insert chest tubes properly.…”
Section: Discussionmentioning
confidence: 99%